WOx matchhead-capped ZnO nanorods for gas-blocking and light-masking behavior. (2nd December 2021) - Huang, Wen-Chang; Wang, Deng-Yi; Lin, Tien-Chai; Kuo, Chih-Chen; Chen, Jyun-Rong; Lee, Chang-Hsueh; Chen, Hsiang
Abstract: In this study, matchhead WOx -capped ZnO nanorods (NRs) were formed by hydrothermal and sputtering processes. In order to examine the morphology and material properties, scanning electron microscopy, transmission electron microscopy, X-ray photoelectron spectroscopy and X-ray diffraction were performed. Amorphous circular-shaped WOx heads were successfully grown on top of ZnO NRs. In order to explore the optical and gas responses of the nanostructures, UV-light responses and H2 gas responses were measured for pure ZnO NRs and WOx /ZnO NRs. The results indicate that the WOx matchhead cap can function like an umbrella to block the light absorption and gas reaction. Furthermore, the light and gas response times were lengthened due to the coverage of the WOx match head. WOx matchhead/ZnO nanocomposites can function as light and gas modulation components for optoelectronic devices.